Metal‐Free Three‐Component Assembly of Fully Substituted 1, 2, 3‐Triazoles. Issue 8 (4th July 2018) - Ahamad, Shakir; Kumar, Anuj; Kant, Ruchir; Mohanan, Kishor
Abstract: A practical domino three‐component protocol involving aldehydes, amines, and α‐diazo‐β‐ketosulfones provides efficient access to fully substituted 1, 2, 3‐triazoles. The process proceeds through a tandem Schiff‐base formation and 1, 3‐dipolar cycloaddition to generate a key sulfonyltriazoline intermediate, which subsequently undergoes an oxidative aromatization with the aid of air or iodine. The three‐component protocol obviates the need of expensive metal catalysts, proceeds under mildly basic conditions, and tolerates a wide range of synthetically useful (hetero)aryl and aliphatic aldehydes, and functionalized amines. Abstract : 123… and cyclize ! An efficient three‐component reaction involving aldehydes, amines, and diazomethylsulfones is reported, leading to the metal‐free synthesis of fully substituted 1, 2, 3‐triazoles. The domino reaction proceeds through a tandem Schiff‐base formation, 1, 3‐dipolar cycloaddition, and oxidative aromatization sequence. The use of readily available and inexpensive starting materials and mild reaction conditions render this strategy a broadly applicable method for the synthesis of fully decorated triazoles.